DAYA DUKUNG BUDIDAYA IKAN KERAPU PADA KERAMBA JARING APUNG TELUK AWANG DAN TELUK BUMBANG, NTB - Lydia Safriyani Marpaung; Yusli Wardiatno; Isdradjad Setyobudiandi; Taslim Arifin (Jurnal Teknologi Perikanan dan Kelautan, 2018)
The carrying capacity is potential of the waters fot utilize coastal or ecosystem resources without cousing damage dan sustainable. This study aims to determine carrying capacity of the water for accommodate the waste from grouper cultivation activities in floating net in Awang Bay and Bumbang Bay. This research was conducted from April until novemver 2015. The research method used is survey method with direct measurements in Awang Bay and Bumbang Bay waters. Carrying capacity analysis used to estimated loading waste the waters from antropogenic and from grouper cultivation activities. The calculation result carrying capacity in Awang Bay and Bumbang Bay waters from N antropogenic waste are 39,14 kg/day, NH3 average concentration is 0,0081 mg/l in Awang Bay and 0,0062 mg/l in Bumbang Bay. The estimated of floating net can be used in Awang Bay are 67 units and 248 units of floating net can be used in Bumbang Bay.